PPeran Sekolah Islam Terpadu Dalam Pembentukan Karakter Religius Siswa - Tanjung, Rahmadani; Lubis, Maulida Rizki (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2024)
Formation of Students' Religious Character (a case study at SDIT Darul Hasan Padangsidimpuan). Therefore, the purpose of this study is to describe and analyze the extent of the role of an integrated Islamic school in the formation of students' religious character. The research method used in this research is descriptive method which is supported by questionnaire data collection techniques, observations, and interviews. The population in this study amounted to 100 students, and a sample of 20% of the population was taken, namely 20 students with percentage data analysis. The results of this study are based on calculations using the percentage formula, the results of the study are categorized as having a very important role. So from the test results it can be seen that there is a very strong and significant role between the role of integrated Islamic schools in the formation of students' religious character. so that in this case study it can be concluded that the Integrated Islamic School can be a forum for the formation of the religious character of students, especially elementary schools.